Emerging role of the endoplasmic reticulum in peroxisome biogenesis - Agrawal, Gaurav; Subramani, Suresh (Frontiers in Physiology, 2013)
During the past few years, we have witnessed a paradigm shift in our long-standing concept of peroxisome biogenesis. Recent biochemical and morphological studies have revealed a primary role of the endoplasmic reticulum (ER) in the de novo formation of peroxisomes, thus challenging the prevalent model invoking growth and division of pre-existing peroxisomes. Importantly, a novel sorting process has been recently defined at the ER that segregates and assembles specific sets of peroxisomal membrane proteins into distinct pre-peroxisomal vesicular carriers (ppVs) that later undergo heterotypic fusion to form mature peroxisomes. Consequently, the emerging model has redefined the function of many peroxins (most notably Pex3, Pex19 and Pex25) and assigned them novel roles in vesicular budding and subsequent peroxisome assembly. These advances establish a novel intracellular membrane trafficking route between the ER and peroxisomes, but the components remain elusive. This review will provide a historical perspective and focus on recent developments in the emerging role of the ER in peroxisome biogenesis.